KREATIVITAS MENGAJAR GURU DAN PERHATIAN ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA PADA MASA PANDEMI - Taufiq Tsany Mahmud; Jonet Ariyanto Nugroho; Khresna Bayu Sangka (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2022)
This study aims to determine the effect of teacher creativity and parent attention contributions to learning motivation of students, teacher creativity on the learning motivation, and the effect of parent attention to the learning motivation. This research is a descriptive quantitative with the pupulation is student from SMKN in Sukoharjo regency, with number of sample was 343 student. The results of this study obtained that the F-count is higher than the F-table (67.068 > 3.00), so that the two independent variables have a simultaneous effect. The results of the T-count variables for teacher instructional creativity and parental attention were 3.802 and 8.434, respectively. Both are above the T-table (1.966). So that the two independent variables have a partial effect on students' learning motivation.